Perancangan Perangkat Lunak Manajemen Keuangan Pribadi Berbasis Mobile Hybrid - Suharjanto Utomo; Dede Badru Jaman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The rapidly developing technology becomes a very supportive means to handle various problems that arise in managing a personal finance. The importance of managing personal financial activities for someone is not a simple thing. To avoid a serious financial problem, it needs a good financial planning. Financial planning in budgeting, management control, funds storage that is owned for the effective and efficient financial decision. The purpose of this research is to build A Personal Finance Software that can help the user in managing personal finances, especially in doing the transaction records of their income and expenditure, which it will be able to show the results of the financial report. This software is designed uses waterfall method and built by mobile hybrid technology from Apache Cordova on client-side, Framework Laravel on server-side and PostgreSQL as database. According to result of implementation, the personal financial management application can be used easily, effectively and efficiently by the users.